Monetary policy shocks in a DSGE model with a shadow banking system - Fabio Verona (2011)
This paper is motivated by the recent nancial crisis and addresses whether a too low for too long interest rate policy may generate a boom-bust cycle. We suggest a model in which a microfounded shadow banking sector is included in an otherwise state-of-the-art DSGE model.When faced with perverse incentives, financial intermediaries within the shadow banking sector can divert a fraction of stockholders' profits for their own benets and extend credit at a discounted rate. The model predicts that long periods of accommodative monetary policy do create thepreconditions for, but do not cause per se, a boom-bust cycle. Rather, it is the combination ofa persistent monetary ease with microeconomic distortions in the financial system that causes a boom-bust.